A Mindful Leader: Mindfulness Strengthens the Leadership Ability of the Leaders in Higher Education Institute - Burmansah Burmansah; Komang Sutawan; Heldy Ramadhan Putra P; Asep Ramadhan (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to describe the practice of leader's mindfulness, which affects leadership ability. This research was conducted at Higher Education School in France. The study used the qualitative research method of a single case study. The data collection techniques used were observation, interviews, and documentation. The procedures in the study had six steps: plan, design, prepare, collection of the data, data analysis, and share. Analysis of the study was done with data validity testing using a data source, method, technique triangulations by pattern matching and used Nvivo 12 Plus. The result of the research shows that the leader develops mindfulness practice in his daily routine through mindfulness values and leadership actions. The training increases leadership's ability to develop concentration and decision-making by practising the formal and informal practice of mindfulness. The Practice brings the leadership ability to create relationships with the community and develop compassion and nonjudgmental attention in leadership activities. The research can benefit the practice of educational leadership to develop their leader's abilities to challenge the status quo in their workplace-based mindfulness. It is how the leader sets mindfulness practice on their leadership practice.